2016
DOI: 10.1097/md.0000000000005773
|View full text |Cite
|
Sign up to set email alerts
|

Could lengthening minocycline therapy better treat early syphilis?

Abstract: Syphilis is a sexually transmitted disease caused by Treponema pallidum. Minocycline, a representative tetracycline derivative, has the greatest antimicrobial activity among all tetracyclines. There are few reports about treating syphilis with minocycline because there is a lack of efficacy data from controlled trials. We compared the rates of serological cure in patients with early syphilis who were treated with minocycline or benzathine penicillin G (BPG).During the study period, a total of 40 syphilis patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Our study compared the efficacy of minocycline in the treatment of syphilis and found that the treatment effect of minocycline was similar to that of benzathine penicillin. Shao et al 17 reported that after the two years follow-up, the serological cure rate of the minocycline four week treatment group (87.34%) was even slightly higher than that of benzathine penicillin (77.50%). Besides, studies have been carried out that an oral loading dose of 200 mg of minocycline, followed by 100 mg twice daily for 15 days, was the treatment for syphilis patients, and as a result, all patients had satisfactory responses to serological tests during followup for as long as one year; in this study, the drug was well tolerated and no major unpleasant side effects were noted.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our study compared the efficacy of minocycline in the treatment of syphilis and found that the treatment effect of minocycline was similar to that of benzathine penicillin. Shao et al 17 reported that after the two years follow-up, the serological cure rate of the minocycline four week treatment group (87.34%) was even slightly higher than that of benzathine penicillin (77.50%). Besides, studies have been carried out that an oral loading dose of 200 mg of minocycline, followed by 100 mg twice daily for 15 days, was the treatment for syphilis patients, and as a result, all patients had satisfactory responses to serological tests during followup for as long as one year; in this study, the drug was well tolerated and no major unpleasant side effects were noted.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, we suspected that primary syphilis was also sensitive to the treatment of minocycline. Moreover, Shao et al 17 compared different courses of minocycline treatment and found that the serological cure rate of minocycline four week treatment (87.34%) was superior to that of minocycline two week treatment (72.73%). At present, there are few studies on the treatment of syphilis with minocycline, which means the further research and evaluation of minocycline efficacy still need to be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors recommend increasing the dose in cases of poor general health conditions. For resistant cases or relapses, prolonged therapy with high doses of penicillin is suggested[20]. In the present case, the patient was diagnosed with malignant syphilis accompanied with neurosyphilis, and he was initially treated with 60 million units of penicillin daily for 10 d, in view of the fact that crystalline penicillin was able to cross the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…While intramuscular 2.4 million units benzathine penicillin G single dose remains the gold standard of treatment, minocycline has been shown to be an effective alternative therapy for early syphilis if penicillin is unavailable. 5…”
Section: Skimages An Unusual Clinical Presentation Of Cutaneous Syphilismentioning
confidence: 99%